Improving out‐of‐hospital notification in traumatic cardiac arrests with novel usage of smartphone application - Geoffrey S. Kelly; Drew Clare (Journal of the American College of Emergency Physicians Open)
Abstract Introduction Timely out‐of‐hospital notifications in patients with traumatic cardiac arrest are associated improvements in mortality. Details surrounding these events are often limited, and decisions to perform advanced resuscitative procedures must be made based on limited data. This study evaluated the ability of a mobile application (app) called Citizen (sp0n Inc., New York, NY) to address these issues by providing a novel, secondary source of out‐of‐hospital information in traumatic cardiac arrest. Citizen sends notifications to mobile devices in response to nearby detected public safety events, and we sought to evaluate its utility in prenotification for traumatic cardiac arrest. Methods This was a retrospective observational study. Patients ≥ 15 years of age with traumatic cardiac arrest attributed to penetrating trauma were included. The 2 coprimary outcomes observed were the time difference between the app notification and emergency medical services notification, and the app's success rate in generating a notification for each patient in traumatic cardiac arrest. Results From February 2, 2019 to October 10, 2019, there were 43 patients who met the criteria for this study. On average, the Citizen app notification arrived 12.9 minutes before emergency medical services radio notification (95% confidence interval, 9.2–16.6; P < 0.001). Citizen generated a notification for 36 of 43 patients (84%). Conclusion The Citizen app generates earlier notifications in traumatic cardiac arrest compared with standard radio communications. It also provides a previously unavailable secondary source of information for making rapid resuscitative decisions upon the arrival of the arresting patient to the emergency department. Further research is needed to determine how to optimally integrate the app into existing trauma systems.